Increasing Speaking Ability Using Visual Media (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
The present study was conducted in order to describe the implementation of visual media in teaching speaking. The researcher used Classroom Action Research design and applied it in teaching of speaking at ten grade of Madrasah Aliyah Kepahiang. The finding of this research indicated that the visual media was successful in increasing students’ speaking ability. In cycle I the score was 68.50 and in cycle II 76.33. Besides, the students have the positive response toward the implementation of visual media. Rapid development of science and technology today has demanded all parties to adjust and follow these developments. Nowadays, the use of media in language learning is very important. It will make the teaching and learning process be more attractive and effective. In learning, media is an aid which is able to help teacher in their teaching activity.